PENGARUH GREEN HUMAN RESOURCE MANAGEMENT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN HOTEL MERCURE DI JAKARTA - Nurizahara Romadhania; Netania Emilisa; Devi Pujiati (Journal of Applied Management and Accounting Science, 2023)
The coronavirus (COVID-19), which arrived in early 2020, is transforming the way people live and work, as well as affecting businesses and organizations in every industry. In the hospitality sectors, employees play a decisive role in ensuring that guests have an enjoyable stay. Therefore, it is essential for each employee to strive for work improvement. This study looked at how job satisfaction and organizational citizenship behavior were affected by green human resource management and quality of life at work. There were 149 responses to the survey. Instrumental tests like validity and reliability and hypothesis testing with SPSS and SEM program analysis were used to analyze this research. In order to confirm the instrument's validity and dependability, this study examines employee perceptions at Hotel Mercure Jakarta. The findings demonstrated that job satisfaction, quality of work life, and organizational citizenship behavior are all positively impacted by green human resource management.